2005
DOI: 10.1111/j.1468-1331.2005.01090.x
|View full text |Cite
|
Sign up to set email alerts
|

Absence of spinocerebellar ataxia type 3/Machado–Joseph disease within ataxic patients in the Czech population

Abstract: Although spinocerebellar ataxia type 3 (SCA3)/Machado-Joseph disease is the most common type of SCA worldwide, we did not identify any cases of the disease amongst SCA patients in the Czech population. It has been proposed that the prevalence of large normal alleles correlates with the frequency of various types of SCA. We have therefore attempted to resolve the absence of SCA3 in our population by investigating, within 204 normal chromosomes, the frequency and nature of CAG repeats as well as two intragenic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 46 publications
0
16
2
Order By: Relevance
“…4A). The difference in the frequency of large ANs between the present study and other studies involving Japanese [9], Indian [10], Czech [11] populations and a combined population comprised of Acadian, Black, Caucasian, Inuit and Thai [21] is shown in table 1.…”
Section: Resultscontrasting
confidence: 61%
See 1 more Smart Citation
“…4A). The difference in the frequency of large ANs between the present study and other studies involving Japanese [9], Indian [10], Czech [11] populations and a combined population comprised of Acadian, Black, Caucasian, Inuit and Thai [21] is shown in table 1.…”
Section: Resultscontrasting
confidence: 61%
“…The most common allele contained 14 CAG repeats, which was also the most common allele found in the studies of Limprasert et al [21] and Takano et al [9]. The frequency of large ANs (>27 repeats) was 0.28, which is higher than the frequency in previously studied populations [9-11,21]. …”
Section: Discussionmentioning
confidence: 55%
“…SCA 3 is the most common type overall with a frequency of about 21%. Outside of Asia the frequency of families with SCA 3 varies from a high of more than 60% in Portugal and Brazil to a low of less than 5% in South Africa and no cases found in a Czech population [7,8]. SCA 3 represents about 20% of autosomal dominant ataxias in the United States.…”
Section: Discussionmentioning
confidence: 99%
“…According to this study we found alleles with a size equal to or greater than 27 (CAG)n in the MJD gene, and MJD is the most frequent ataxia among patients. These findings have an epidemiological interest as these alleles appear to be in haplotypes that have a great potential for expansion by gene conversion 19,[36][37][38][39][40] .…”
Section: Discussionmentioning
confidence: 99%
“…Fluorescent labels were selected based on the normal allele size ranges described above for each locus, while taking care to ensure that loci with overlapping size ranges were given different labels. The following reactions were carried out: one triplex reaction with 1.5 pmol of each primer for SCA1 (36), SCA2 (10) and SCA6 (18); a single reaction with 12pmol of each SCA3 primer (SCA3F 5'NED-CTGGCCTTTCACATGG 3' and SCA3R 5' CCA-GTCACTACTTTGATTCGTG 3') and a reaction with 15 pmol of each SCA7 primer (SCA7F 5'VIC-TTGTAGGAGCGGAAAGAAT-GTC 3'and SCA7R 5' CTTCAGGACTGGGCAGAGG 3'). The last two pairs of primers (SCA3 pair and SCA7 pair) were designed for the present study.…”
Section: Pcr Amplification and Capillary Electrophoresismentioning
confidence: 99%